2017
DOI: 10.2147/opth.s123273
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of peripapillary retinal nerve fiber layer thickness and macular thickness in anisometropia using spectral domain optical coherence tomography: a prospective study

Abstract: PurposeTo study whether there is a difference in central macular thickness (CMT) and peripapillary retinal nerve fiber layer (RNFL) thickness between the two eyes of individuals having anisometropia >1 diopter (D) using spectral domain optical coherence tomography (OCT).Material and methodsOne hundred and one subjects, 31 with myopic anisometropia, 28 with astigmatic anisometropia, and 42 with hypermetropic anisometropia, were enrolled in the study. After informed consent, detailed ophthalmological examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
2
9
1
Order By: Relevance
“…Another limitation of our Journal of Ophthalmology study is that there was a difference in terms of astigmatism between two groups. Although there are publications in the literature that astigmatism may not affect RNFL measurements [24,25], the significant difference between the two groups in terms of astigmatism is the limitation of our study.…”
Section: Discussionmentioning
confidence: 81%
“…Another limitation of our Journal of Ophthalmology study is that there was a difference in terms of astigmatism between two groups. Although there are publications in the literature that astigmatism may not affect RNFL measurements [24,25], the significant difference between the two groups in terms of astigmatism is the limitation of our study.…”
Section: Discussionmentioning
confidence: 81%
“…OCT offered reliable and accurate crosssectional imaging of the retinal structure and evaluation of the retinal changes accompanying amblyopia. However, evidences for direct retinal changes in amblyopia remain controversial [9,16]. In the current study we compared the peripapillary RNFL thickness, macular parameters, and GCL+ thickness of amblyopic eyes (group A) with that of fellow normal eyes (group B) and normal control eyes of non-amblyopic subjects (group C) using SD-OCT.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies examined the amblyopic retinal thickness using OCT and the degree of retinal involvement accompanying amblyopia is controversial. Some of these studies reported no differences between amblyopic and their healthy normal fellow eyes [6][7][8][9][10], whereas others reported significant differences between amblyopic and healthy eyes [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the macular vessel system, our data showed unchanged mean macular thickness in unilateral anisometropic amblyopes and in successfully treated anisometropic amblyopic children after adjustment for the AL. Many studies using OCT have examined retinal thickness of amblyopia and evaluated the reversal of difference after treatment with varied methodologies [33][34][35][36][37] . It is reported studies that showed difference in retinal thicknesses tend to show increased thickness associated with amblyopia.…”
Section: Discussionmentioning
confidence: 99%